Catalytic Applications of Recent and Improved Covalent Organic Frameworks - Sharma, Venu; Nemiwal, Meena; Kumar, Dinesh (Mini-Reviews in Organic Chemistry, 2022)
Covalent Organic Frameworks (COFs) are porous crystalline materials that have emerged as promising molecular materials in optoelectronics, catalysis, and gas storage applications. COFs exhibit unique features, such as adaptability for various substrates, high chemical stability, tunability, ease of working, and recyclability, making them efficient catalysts. The current mini-review article discusses the synthesis and applications of COFs as catalysts. We hope that the present review will be highly beneficial for researchers working in the area of COFs and their applications in catalysis.
Keywords: heterogeneous catalysis